A facile synthesis of molybdenum carbide nanoparticles-modified carbonized cotton textile as an anode material for high-performance microbial fuel cells. Issue 70 (4th December 2018) - Zeng, Lizhen; Zhao, Shaofei; Zhang, Lixia; He, Miao
Abstract : A novel macroscale porous structure electrode, molybdenum carbide nanoparticles-modified carbonized cotton textile (Mo2 C/CCT), was synthesized by a facile two-step method and used as anode material for high-performance microbial fuel cell (MFC). Abstract : A novel macroscale porous structure electrode, molybdenum carbide nanoparticles-modified carbonized cotton textile (Mo2 C/CCT), was synthesized by a facile two-step method and used as an anode material for high-performance microbial fuel cells (MFCs). The characterization results show that the carbonized cotton textile modified with Mo2 C nanoparticles offers a great specific surface area (832.17 m 2 g −1 ) for bacterial adhesion. The MFC using Mo2 C/CCT anode delivers the maximum power density of 1.12 W m −2, which is 51% and 116% higher than that of CCT and unmodified carbon felt anodes under the same conditions. The high power density is mainly due to the Mo2 C nanoparticles with good biocompatibility and high conductivity and superior electrochemical activity, as well as the macroscale porous structure of carbonized cotton textile, which facilitate the formation of electroactive biofilm and improve the electron transfer. This paper introduces a feasible way to synthesize cost-effective and high-performance anode materials for MFCs.